Proceedings of the 22nd International Conference on World Wide Web 2013
DOI: 10.1145/2488388.2488471
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and modeling of eye-mouse behavior in the presence of nonlinear page layouts

Abstract: As search pages are becoming increasingly complex, with images and nonlinear page layouts, understanding how users examine the page is important. We present a lab study on the effect of a rich informational panel to the right of the search result column, on eye and mouse behavior. Using eye and mouse data, we show that the flow of user attention on nonlinear page layouts is different from the widely believed top-down linear examination order of search results. We further demonstrate that the mouse, like the ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 19 publications
2
66
0
Order By: Relevance
“…Further works showed that eye-mouse coordination [13] and gaze position [18] could be predicted to some extent by mouse movements, also in the context of non-linear layout SERPs [25]. Outside the search domain, [5] showed in a debugging task that mouse cursor behaviour was a significant indication of the level of difficulty and performance, and the observed cursor patterns were found comparable with the gaze patterns.…”
Section: Related Workmentioning
confidence: 98%
“…Further works showed that eye-mouse coordination [13] and gaze position [18] could be predicted to some extent by mouse movements, also in the context of non-linear layout SERPs [25]. Outside the search domain, [5] showed in a debugging task that mouse cursor behaviour was a significant indication of the level of difficulty and performance, and the observed cursor patterns were found comparable with the gaze patterns.…”
Section: Related Workmentioning
confidence: 98%
“…Such data collection se ings are similar to previous studies such as [36]. Meanwhile, we adopt SERP-level satisfaction rather than session-level satisfaction in this paper because most o ine metrics are designed to measure the quality of only one search result page.…”
Section: Figure 1: Data Collection Proceduresmentioning
confidence: 99%
“…Core to their experience and success is the Search Engine Results Page (SERP), with its presentation and design over the years having been subject to much research. With more complex components now becoming commonplace in modern day Web search engines (such as the information card [5,36] or social annotations [35]), much work however still remains on examining how more traditional SERP components (such as result summaries) are designed and presented to end users.…”
Section: Introductionmentioning
confidence: 99%